Making justice visible : war crimes trials, media and memory after World War II - Leiserowitz, Ruth 1958- HerausgeberIn; Malinauskaitė, Gintarė 1985- HerausgeberIn; Vitkus, Hektoras 1976- HerausgeberIn; fibre Verlag (Einzelveröffentlichungen des Deutschen Historischen Instituts Warschau, 2022)
How much has media shaped the perception of war crimes trials and the historical narratives of World War II that were at the center of those proceedings? Has media reporting been influenced by political agenda and affected by the ideological constraints of the corresponding countries? What memories of the past have been recovered or excluded by media coverage? What history of postwar justice was conceived by the work of journalists, filmmakers and other media actors? Do we remember those war crimes trials to this day the way media has envisioned for us to recall them? This volume addresses the multifaceted history of war crimes trials after World War II and analyzes the interrelationship of law, media and memory. It brings together articles of recognized and emerging scholars, offering a wide range of international perspectives. The spotlight is on selected war crimes trials in the Soviet Union, Poland, Yugoslavia, and East and West Germany. The authors discuss how media (mis)represented war crimes trials that took place after World War II. By focusing on these trials as mediated events, the volume shows how media translated those legal proceedings for larger audiences and portrayed the legal principles of the analyzed judicial systems.